Advances in DLL3-targeted therapies for small cell lung cancer: challenges, opportunities, and future directions - Ding, Jianhua; Yeong, Chaihong (Frontiers in Oncology, 2024)
Small cell lung cancer (SCLC) remains one of the most aggressive and challenging malignancies to treat, with limited therapeutic options and poor outcomes. Recent advances in understanding SCLC biology have identified Delta-like ligand 3 (DLL3) as a promising target for novel therapies. This review explores the evolving landscape of DLL3-targeted therapies in SCLC, examining their mechanistic basis, preclinical promise, and clinical development. We discuss various therapeutic modalities, including antibody-drug conjugates (ADCs), bispecific T-cell engagers (BiTEs), chimeric antigen receptor T-cell (CAR-T) therapies, and emerging approaches such as near-infrared photoimmunotherapy (NIR-PIT) and radiopharmaceutical therapy (RPT). The review highlights the challenges encountered in translating these promising approaches into clinical practice, including the setbacks faced by early DLL3-targeted therapies like Rovalpituzumab Tesirine (Rova-T). We also explore potential strategies to overcome these obstacles, emphasizing the need for a more nuanced understanding of DLL3 biology and its role in SCLC pathogenesis. The integration of cutting-edge technologies and interdisciplinary collaboration is proposed as a path forward to optimize DLL3-targeted therapies and improve outcomes for SCLC patients. This comprehensive overview provides insights into the current state and future directions of DLL3-targeted therapies, underscoring their potential to revolutionize SCLC treatment paradigms.